The Effects of CRA/CSA Explicit Instruction for Students with and without Disabilities Taught in an Inclusive Setting - Hinton, Vanessa; Gibbs, Anna; Franklin, Toni (Journal of the American Academy of Special Education Professionals, 2020)
Children with cognitive delays or developmental disabilities are at elevated risk of having a persistent mathematics disability. Students who have difficulty in mathematics display trouble with awareness of numbers and numeric concepts. This is alarming because students who display lower mathematics performance early on in school make smaller gains in mathematics throughout their school years. Researchers show that explicit instruction is effective in teaching students with disabilities mathematics. More research needs to be conducted on brief explicit mathematic interventions using the concrete-representational-abstract sequence which is also referred to as the concrete semi-concrete abstract sequence in mathematics literature that target the skill of counting for students with and without developmental disabilities taught in inclusive settings. In this study, researchers examine the effects of using explicit instruction coupled with the concrete-representational-abstract sequence to teach counting skills to students who received special education services for disabilities in an inclusive setting along with their peers not identified as receiving special education. Implications of these findings are also discussed.